Can Modern and Traditional Hebrew Instruction be Integrated in Jewish Education? An Assessment of Ivrit b’Ivrit Curriculum - Hassenfeld, Ziva R. (Review of religious research, 2025)
This paper presents findings from research conducted over two years examining students’ biblical Hebrew comprehension levels in full-time private Jewish schools. The study included teacher interviews, classroom observations, student assessments, parent surveys, and three rounds of task-based interviews with 43 students focused on reading and translating biblical Hebrew. This paper makes three primary contributions. First, it presents findings on the level of fluency these students have in biblical Hebrew, drawing on a group of students who have been schooled in Ivrit b’Ivrit. Second, it offers portraits of how these students approach the task of translating and comprehending biblical Hebrew. Third, it suggests a novel path forward for biblical Hebrew education in full-time Jewish schools, given the consistently low levels of biblical Hebrew comprehension observed. The results of this study suggest that the Jewish educational community, particularly those invested in full-time Jewish schooling, might consider reforming the goals and purposes of biblical Hebrew education in particular the current Ivrit b’Ivrit model.